Girl, stop apologizing : a shame-free plan for embracing and achieving your goals - Hollis, Rachel; Ludes, Annie (New York, New York HarperCollins Leadership, an imprint of HarperCollins, 2019)
"'I believe we can change the world. But first, we've got to stop living in fear of being judged for who we are.' Rachel Hollis has seen it too often: women not living into their full potential. They feel a tugging on their hearts for something more, but they're afraid of embarrassment, of falling short of perfection, of not being enough. In [this book], bestselling author and founder of a multimillion-dollar media company Rachel Hollis sounds a wake-up call. She knows that many women have been taught to define themselves in light of other people--whether as wife, mother, daughter, or employee--instead of learning how to own who they are and what they want. With a challenge to women everywhere to stop talking themselves out of their dreams, Hollis identifies the excuses to let go of, the behaviors to adopt, and the skills to acquire on the path to growth, confidence, and believing in yourself."--Dust jacket.
Introduction: What if... -- Excuses to let go of. That's not what other women do ; I'm not a goal-oriented person -- I don't have time ; I'm not enough to succeed ; I can't pursue my dream and still be a good mom/daughter/employee ; I'm terrified of failure ; It's been done before ; What will they think? ; Good girls don't hustle -- Behaviors to adopt. Stop asking permission ; Choose one dream and go all in ; Embrace your ambition ; Ask for help! ; Build foundations for success ; Stop allowing them to talk you out of it ; Learn to say no -- Skills to acquire. Planning ; Confidence ; Persistence ; Effectiveness ; Positivity ; Lead-her-ship -- Conclusion: Believe in your dang self!
Includes bibliographical references (pages 215-216).
107195
Keywords: Self-actualization (Psychology) in women; Self-esteem in women; Happiness; Success; Selp-Help -- Motivational & Inspirational; Selp-Help -- Personal Growth -- Success; Religion -- Christian Living -- Women's Interests; Nonfiction; Self-help publications